FUNCTIONAL AND PSYCHOSOCIAL OUTCOMES OF AUTOLOGOUS FASCIA SLING RECONSTRUCTION SURGERY IN A SCHOOL-AGE CHILD WITH CRANIOFACIAL NEUROFIBROMATOSIS TYPE 1 - Putu Laksmi Febriyani; Adinda Widita; Ahmed Mostafa Elsaid Eid (Universitas Airlangga, 2026)
Highlights: This case report demonstrates successful staged craniofacial reconstruction in a pediatric NF1 patient using a static autologous temporal fascia sling. The technique improved eyelid function and facial contour without implants, while enhancing the patient’s self-confidence and quality of life. Complex craniofacial NF1 cases require multidisciplinary management and long-term follow-up. Abstract Introduction: Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder characterized by café-au-lait macules, cutaneous neurofibromas, and possible craniofacial involvement. Although benign, craniofacial NF1 can lead to significant deformity and functional impairment. This report presents the functional, aesthetic, and psychosocial outcomes of autologous temporal fascia sling reconstruction in a school-age child. Case Illustration: A 14-year-old boy presented with progressive swelling of the right hemifacial region since birth, accompanied by facial asymmetry, severe ptosis, visual impairment due to eyelid obstruction, and hearing loss. Radiological examination showed craniofacial involvement without intracranial extension. The patient previously underwent partial debulking, followed by wide excision of residual plexiform neurofibroma and reconstruction with an autologous temporal fascia sling as a second-stage procedure, restoring eyelid function and facial contour. Postoperatively, self-confidence improved and the patient returned to school, although visual and hearing deficits persisted. Discussion: Craniofacial NF1 presents therapeutic challenges due to tumor infiltration, recurrence, and psychosocial impact. Diagnosis is established through a combination of clinical signs, imaging, and histopathology. Surgery remains the primary treatment although it is often challenging to perform thoroughly and carries a risk of recurrence. Early intervention, especially in symptomatic cases, is crucial for improving function, appearance, and quality of life. Conclusion: Craniofacial reconstruction with a static autologous temporal fascia sling in NF1 can provide significant functional and aesthetics improvements. Long-term monitoring is still needed to detect recurrence and complications.